Depletion study and estimation of the withdrawal period for enrofloxacin in pacu (Piaractus mesopotamicus) - Jonas Augusto Rizzato Paschoal; Silvia Pilco-Quesada; Lígia Uribe Gonçalves; José Eurico Possebon Cyrino; Félix Guillermo Reyes Reyes (My University, 2013)
Defining the pharmacokinetic parameters and depletion intervals for antimicrobials used in fish will help in the development of important guidelines for future regulations by Brazilian agencies on the use of these substances in fish farming. This paper presents a depletion study for enrofloxacin (ENR) and its main metabolite, ciprofloxacin (CIP), in pacu (Piaractus mesopotamicus) fillets. The depletion study was carried out under monitored environmental conditions, with the temperature controlled at 27 °C to mimic the fish farming conditions in Brazil. ENR was administered orally via medicated feed for 10 consecutive days at daily dosages of 10 mg/kg body weight (b.w.). The fish were slaughtered at 6, 12, and 24 h and 2, 3, 5, 8, 12, 17, and 24 days after the medication period. Considering a maximum residue limit of 100 μg/kg for the sum of the ENR and CIP residues in the fillet, the results obtained in the depletion study allowed the estimation of a half-life for ENR of 2.75 days and a withdrawal period of 23 days. The results obtained in this study are important for the farming of pacu in tropical regions.
Keywords: Pacu; Piaractus mesopotamicus; Enrofloxacin; Maximum Residue Limit; Residue (chemistry); Withdrawal time; Body weight; Animal science; Ciprofloxacin; Chemistry; Veterinary medicine; Biology; Toxicology; Fishery; Medicine; Pesticide; Antibiotics; Pesticide residue; Microbiology; Agronomy; Biochemistry; Colorectal cancer; Endocrinology; Colonoscopy; Genetics; Cancer; Pacu; Piaractus mesopotamicus; Enrofloxacin; Maximum Residue Limit; Residue (chemistry); Withdrawal time; Body weight; Animal science; Ciprofloxacin; Chemistry; Veterinary medicine; Biology; Toxicology; Fishery; Medicine; Pesticide; Antibiotics; Pesticide residue; Microbiology; Agronomy; Biochemistry; Enrofloxacin; Enrofloxacin; Enrofloxacin; Animals; Animals; Animals; Anti-Bacterial Agents metabolism; Anti-Bacterial Agents metabolism; Anti-Bacterial Agents metabolism; Anti-Bacterial Agents pharmacokinetics; Anti-Bacterial Agents pharmacokinetics; Anti-Bacterial Agents pharmacokinetics; Anti-Bacterial Agents chemistry; Anti-Bacterial Agents chemistry; Anti-Bacterial Agents chemistry; Ciprofloxacin metabolism; Ciprofloxacin metabolism; Ciprofloxacin metabolism; Ciprofloxacin pharmacokinetics; Ciprofloxacin pharmacokinetics; Ciprofloxacin pharmacokinetics; Ciprofloxacin chemistry; Ciprofloxacin chemistry; Ciprofloxacin chemistry; Drug Residues; Drug Residues; Drug Residues; Half-Life; Half-Life; Half-Life; Muscle, Skeletal chemistry; Muscle, Skeletal chemistry; Muscle, Skeletal chemistry; Fluoroquinolones metabolism; Fluoroquinolones metabolism; Fluoroquinolones metabolism; Fluoroquinolones pharmacokinetics; Fluoroquinolones pharmacokinetics; Fluoroquinolones pharmacokinetics; Fluoroquinolones chemistry; Fluoroquinolones chemistry; Fluoroquinolones chemistry; Characiformes metabolism; Characiformes metabolism; Characiformes metabolism; Health Sciences Medicine Pharmacology Antibiotics Pharmacokinetics and Efficacy; Physical Sciences Environmental Science Pollution Pharmaceutical and Antibiotic Environmental Impacts; Life Sciences Biochemistry, Genetics and Molecular Biology Molecular Medicine Antibiotic Resistance in Bacteria